The Imagined Life of an Otaku Collector, or To Be a Cosplay Star - Watts, Mark Leonard (Auckland University of Technology, 2008)
This project explores my relationship with elements of Japanese culture. Central to the project will be the Japanese practice of cosplay (dressing in costume), otaku (geek) subculture and their influences in the worlds of Japanese manga comic books and animated films. It will focus on the importance of kawaii (cute) in Japanese culture. The artworks will explore notions of identity and the ‘space between’. I shall do this through the gathering of Japanese objects which will be fused with my own image. I shall use photography, print and digital manipulation finishing in a sculptural installation referencing pop culture and commercial display. This project will constitute 80% practical work to be presented in a final exhibition piece accompanied by 20% written exegesis.
Keywords: Otaku; Kawaii; Japan; Cosplay; Shokugan; Doll